Multidimensional mechanisms of anxiety and depression in Parkinson’s disease: Integrating neuroimaging, neurocircuits, and molecular pathways - Jihu Zhao; Huafang Jia; Pengju Ma; Deyuan Zhu; Yibin Fang (Pharmacological Research)
Anxiety and depression are common non-motor symptoms of Parkinson’s disease (PD) that significantly affect patients’ quality of life. In recent years, our understanding of PD has advanced through multifaceted studies on the pathological mechanisms associated with anxiety and depression in PD. These classic psychiatric symptoms involve complex pathophysiology, with both distinct features and connections to the mechanisms underlying the aetiology of PD. Furthermore, the co-occurrence of anxiety and depression in PD blurs the boundaries between them. Therefore, a comprehensive summary of the pathogenic mechanisms associated with anxiety and depression will aid in better addressing the emergence of these classic psychiatric symptoms in PD. This article integrates neuroanatomical, neural projection, neurotransmitter, neuroinflammatory, brain-gut axis, neurotrophic, hypothalamic-pituitary-adrenal axis, and genetic perspectives to provide a comprehensive description of the core pathological alterations underlying anxiety and depression in PD, aiming to provide an up-to-date perspective and broader therapeutic prospects for PD patients suffering from anxiety or depression.